HUBUNGAN PEMBERIAN ASI EKSKLUSIF, SUSU FORMULA DAN STATUS BEKERJA IBU DENGAN STATUS GIZI BAYI USIA 0 - 6 BULAN DI KELURAHAN SAWANGAN DAN LIMO KOTA DEPOK - Ghina Nabila Khairunisa, (2023)
Good growth and development for children is influenced by adequate and optimal nutritional intake, one of which includes the consumption of breast milk (ASI) exclusively from the beginning of the baby's birth. When the mother works or the mother does not produce breast milk, the use of formula milk can be an option when the mother cannot provide breast milk. This study aims to analyze the relationship between exclusive breastfeeding, formula milk and mother's working status with the nutritional status of infants aged 0-6 months in Sawangan Baru, Sawangan Lama and Limo Urban Villages, Depok City. This research method is analytic observational with cross sectional design. The population in this study were all mothers who breastfed in Sawangan Baru, Sawangan Lama and Limo urban villages in Depok City. The research sample was taken using convenient sampling technique of 78 people. Data collection was done using a questionnaire, while data analysis used the chi-square test. The results showed that there was a significant relationship between exclusive breastfeeding and the nutritional status of infants aged 0-6 months (p-value = 0.023) and the relationship between formula milk and the nutritional status of infants aged 0-6 months (p-value = 0.015). However, there was no significant relationship between the working status of mothers and the nutritional status of infants aged 0 - 6 months (p-value = 0.541). The suggestion of this study is to advise mothers to pay attention to the nutrients needed by babies for optimal growth and development.